Felipe Poey of Cuba and His “Memorias” - M. K. Jacobson (Hello World!, 1977)
Felipe Poey y Aloy (1799-1891), the great Cuban naturalist, malacologist, and savant, in spite of his many serious contributions to many fields of knowledge (see Boss and Jacobson, 1975, for details of his life, personality, and works) was a cheerful, poetic, and at times playful and unconventional individual. His cheerful, funloving temperament appears often in his most important published works, Memorias sobre la Historia natural de la Isla De Cuba.